Pengelolaan Fasilitas Wisata Dan Dampaknya Terhadap Pengalaman Wisatawan di Taman Wisata Alam Mangrove PIK 2: (Tourism Facility Management and Its Impact on Tourist Experience at PIK 2 Mangrove Nature Tourism Park) - Ellen Aurelie Basuki; Annisa Tussholia; Syarif Hidayat; Muhammad Syafarul Adnan (OGZ Research & Publishing, 2025)
Abstract:This study aims to analyze the management of tourist facilities and its impact on the tourist experience at the Pantai Indah Kapuk 2 Mangrove Nature Tourism Park (TWA), North Jakarta. This area is an ecotourism destination that combines conservation and recreation, but the increasing number of visitors demands optimal facility management to avoid disrupting the ecosystem's balance. This study used a descriptive qualitative method, with data sources obtained through documentation, scientific journals, and interviews with three tourists. The results indicate that while the main facilities, such as pedestrian paths, restrooms, gazebos, and seating areas, are considered adequate, there are still shortcomings in aspects of cleanliness, lighting, and directional signs. Supporting facilities such as photo spots, observation towers, and cafes contribute to the attraction, but environmental education remains under-recognized. Good facility management has been shown to positively impact tourist comfort and satisfaction, while deficiencies in maintenance detract from the quality of the tourist experience. This study recommends improving cleanliness, providing educational resources, improving accessibility, and promoting sustainable ecotourism. With sustainable management, the PIK 2 Mangrove TWA has the potential to become an urban ecotourism icon offering not only recreation but also environmental education.Methodology: Descriptive qualitative method, to gain a deep understanding of the phenomenon under study through data collection in the form of words, actions, and documents.Research Results: The analysis shows that facility management has a direct influence on tourist experiences. Well-maintained facilities create a sense of comfort and safety, while poorly maintained facilities reduce impressions and satisfaction.Keywords: Tourism Facility Management, Tourist Experience, PIK 2 Mangrove Nature Tourism Park